(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
5-HT receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on 5-HT receptors [201] and subsequently revised [183]) are, with the exception of the ionotropic 5-HT3 class, GPCRs where the endogenous agonist is 5-hydroxytryptamine. The diversity of metabotropic 5-HT receptors is increased by alternative splicing that produces isoforms of the 5-HT2A (non-functional), 5-HT2C (non-functional), 5-HT4, 5-HT6 (non-functional) and 5-HT7 receptors. Unique amongst the GPCRs, RNA editing produces 5-HT2C receptor isoforms that differ in function, such as efficiency and specificity of coupling to Gq/11 and also pharmacology [41, 500]. Most 5-HT receptors (except 5-ht1e and 5-ht5b) play specific roles mediating functional responses in different tissues (reviewed by [479, 395]).